2014
DOI: 10.1186/1757-4749-6-30
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing of multidrug resistant novel Clostridium sp. BL8 reveals its potential for pathogenicity

Abstract: BackgroundThe human gut microbiome is important for maintaining the health status of the host. Clostridia are key members of the human gut microbiome, carrying out several important functions in the gut environment. Hence understanding the role of different Clostridium species isolated from human gut is essential. The present study was aimed at investigating the role of novel Clostridium sp. isolate BL8 in human gut using genome sequencing as a tool.FindingsThe genome analysis of Clostridium sp. BL8 showed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Since its invention by Rothberg et al (2011), Ion Torrent sequencing technology has been successfully applied to complete genomic sequencing, such as in Clostridium sp. BL8 (with Ion Torrent PGM™) (Marathe et al, 2014), and clear characterization of drug-resistant genes, such as in Mycobacterium tuberculosis (Daum et al, 2014). Results can be obtained within five days, comparable to the turnaround time required by current drug sensitivity testing (DST) (Daum et al, 2014).…”
Section: Whole Genome Sequencing Is a Feasible Way To Investigate Thementioning
confidence: 77%
“…Since its invention by Rothberg et al (2011), Ion Torrent sequencing technology has been successfully applied to complete genomic sequencing, such as in Clostridium sp. BL8 (with Ion Torrent PGM™) (Marathe et al, 2014), and clear characterization of drug-resistant genes, such as in Mycobacterium tuberculosis (Daum et al, 2014). Results can be obtained within five days, comparable to the turnaround time required by current drug sensitivity testing (DST) (Daum et al, 2014).…”
Section: Whole Genome Sequencing Is a Feasible Way To Investigate Thementioning
confidence: 77%
“…Few studies reported from India on genome sequencing and annotation of gut bacterial isolates helped us understand their pathogenic characters such as virulence patterns, multi-drug resistance etc. A study carried out by Marathe et al 2014 on genomic characterization of Clostridium sp. isolated from human gut, showed the presence of various genes responsible for Multi-Drug Resistance (MDR).…”
Section: Bacterial Isolation and Genomicsmentioning
confidence: 99%
“…Strain BLPYG-8 T exhibited thiosulfate- and sulfur-reducing activity but did not exhibit sulfite-, sulfate- or nitrate-reducing activity, and was catalase- and oxidase-negative. The whole-genome sequence analysis of strain BLPYG-8 T also revealed the absence of the genes responsible for all the said activities (Marathe et al , 2014). Strain BLPYG-8 T tolerated bile up to 0.3 % (w/v).…”
mentioning
confidence: 99%
“…These antibiotics included vancomycin, colistin, penicillin G, ampicillin, tetracycline, gentamicin, streptomycin, kanamycin, cotrimoxazole, amikacin and chloramphenicol. The genome sequencing also revealed the presence of antibiotic resistance genes against the tested antibiotics as well as other non-tested antibiotics (Marathe et al , 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation